Financial distress, value of firm, trilemma index dan investment decision studi pada perusahaan pertambangan global besar - Junivar, Mutiara Syahada; Ariefianto, Moch. Doddy; Trinugroho, Irwan (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study was to determine the relationship between financial distress, value of firm and investment decision in the world's largest mining companies. Investment decision in a company is very important in developing the company, it can be by doing business expansion or other things. This research uses quantitative methods. The independent variables in this study are financial distress, firm value and trilemma index. the financial distress coefficient is negative -0.04 significant with a p-value of 0.021 for investment decisions. Financial distress has a negative influence on investment decisions in large mining companies around the world in 2010-2019, which means that in the world's large mining companies, companies that have a financial downturn in their companies tend to make investment decisions with the aim of restoring the company's financial condition. The point is, financial distress here can also occur not because after the company makes an investment decision, the company will experience a financial downturn, this can happen one of them because by making an investment decision it can make the company's finances seem to be reduced but financial conditions can be reduced. by the company in making investments.